Peningkatan Pengetahuan Dan Kemampuan Manajemen Stres: Sebuah Pendekatan Penyuluhan Dan Evaluasi - Galih Panjalu Pramono; Fanniya Dyah Prameswari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Alumni Association is an organization in Semarang City, Central Java, which consists of graduates of SMA N Semarang with various backgrounds and work sectors. In the context of human resource management, members face pressure and stress that may interfere with their productivity and well-being, due to limited knowledge in managing work stress. Counseling on work stress management was successfully carried out with the participation of 30 participants, which increased their understanding significantly. Even though there are obstacles such as limited time and differences in participant backgrounds, this activity succeeded in improving their skills in managing stress in the workplace, and it is hoped that similar activities can be carried out regularly to continue to improve the quality of life and productivity of alumni members and their employees